Clinical Ethics Support Provided to Interdisciplinary Rehabilitation Teams in Quebec: A Qualitative Study - Déry, Julien; Amirova, Jamila; Kardan, Sina; Tito, Noémie; Zhu, Zun; Hunt, Matthew; Hudon, Anne (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
Introduction: Rehabilitation is a health care service focusing on the restoration and maintenance of function and is often undertaken by interdisciplinary teams. Rehabilitation care providers encounter ethical issues and concerns that require attention and resolution. Clinical ethics services (CES) provided by ethics consultants aim to support teams facing ethical challenges. The objective of this study was to explore the experiences and perspectives of individuals providing CES to interdisciplinary rehabilitation teams in Quebec health care centres.Methods: We conducted a qualitative descriptive study and interviewed individuals who provide CES in all 22 integrated health care centres in the province of Quebec. Interview transcripts were examined using constant comparative techniques and inductive thematic analysis.Results: Rehabilitation teams requested CES to address a range of issues, from conflicts between upholding patient autonomy and promoting safety to challenges arising due to structural gaps in care trajectories. However, ethics requests from rehabilitation teams were described as much less frequent than those received from teams working in acute care settings. Forms of CES provided to rehabilitation teams included accompaniment, ethical deliberation and mediation. Participants highlighted challenges providing ethics support, such as limited visibility of their services amongst rehabilitation teams and insufficient resources available to extend the reach of CES.Conclusion: Despite encountering challenges, ethics consultants offer diverse forms of support to interdisciplinary rehabilitation teams in Quebec. Further research is needed to better understand the range of ethical issues arising in rehabilitation, as well as the impact that CES support can have on how situations unfold and how they are experienced by all involved.